Exploring the Alignment between Digital Strategies and Educational Practices in Higher Education Infrastructures - Egil Øvrelid (Education Sciences, 2022)
Higher education is a key pillar in constructing new knowledge economies for the 21st century, and the digitalization of higher education is a central focus area for national authorities. Visionary discourses from authorities state that the decision-making authority for digital strategies should be centralized to the domain of management. Digitalization is, however, driven by key features of modern technology and may also lead to the transformation of traditional educational methods as well as educational practices. Since the university contains several disciplines, different strategies can be used when products or processes within the disciplines are digitalized. It is important to consider in the ways that different disciplines can proceed to digitalize their educational practices. Based on these interests, our research question is as follows: how do digital strategies in higher education emerge, and how do they align with the educational context? Through a qualitative case study with interviews, participation in workshops, and document analyses, we investigated two digitalization efforts in the fields of medicine and law. We found that the two classical disciplines’ strategic approaches differed substantially. Based on the findings, our main contribution is a digitalization model with two archetypes, namely digital transformation strategy and digital innovation strategy. The model highlight the main object of the respective strategies, but also the institutional reaction to digitalization efforts. An implication from our study is the demonstration of how specific faculties adapt digital strategies to educational practices. This may sometimes lead to the transformation of educational practices, while other times more incremental moderate changes may be implemented. From a practical point of view, policymakers, politicians, educational management, and professionals need knowledge and expertise about the implications of digital strategies for educational practices. Our contribution, we propose, strengthens the understanding of strategies within digital infrastructures in higher education.